Interactive Learning: The Use of Multimedia with Hybrid Models in Balinese Language Subjects for Grade VII Students - I Gede Ardi Suryadharma; I Nyoman Jampel; I Komang Sudarma (Universitas Pendidikan Ganesha, 2021)
The cultural shift in the era of globalization has greatly influenced the Balinese culture which is deeply ingrained for the Balinese. Therefore, innovative learning media is needed as an effort to prevent this cultural shift. This study aims to develop an interactive multimedia hybrid learning model in Balinese language subjects for seventh-grade junior high school students. Interactive learning multimedia developed using the Articulate Storyline 3 application because this application has features that are easy to use. This interactive multimedia development uses the ADDIE development model which consists of the analysis, design, development, implementation, and evaluation stages. The results of the validity of interactive multimedia development will be presented in five main points which include: subject matter experts, learning design experts, learning media experts, individual trials, and small group trials. The subjects of this study included experts, namely 1 subject matter expert, 1 learning design expert, 1 learning media expert, 3 individual test subjects, and 9 small group trial subjects. The methods used in collecting data are observation methods, interview methods, and questionnaire methods. The data analysis technique in this research is descriptive qualitative and descriptive quantitative. The data collection instrument in this study was using a questionnaire. The results of the calculation of the value of the experts (subject experts, instructional design, instructional media), individual trials, and small group trials get very good qualifications. Based on these qualifications, it can be concluded that the interactive multimedia hybrid learning model in Balinese class VII subjects is feasible to be applied to support the learning process.